Problems of democratization in XXI century: The case of Russia resume - Susolia Artem (Srpska Politička Misao)
The main research objective of the article was to assess the nature and the way of the transformation of Russia's political system over the past 23 years. The process of transformation taking place there, was analyzed in the context of Samuel Huntington's Third Wave paradigm, which, in the opinion of the author, was considered the most corresponding to the changes occurring in Russian Federation after 2000. In connection with the above, an attempt was made to answer the following research questions: Firstly, what was the specificity of the democratization of the political system during last 23 years in Russia? Secondly, whether a de facto retreat from democratization began in the first decades of the 21st century? Thirdly, whether the political system of the Russian Federation can now be considered fully authoritarian? Democratic transformation in Russia in the near future is assessed as problematic, and the possible scenario of such events seems non-representational at this moment. As can be seen from the in-depth analysis, democratization is not a state achieved once and for all, it is an extremely complex form and requires constant, systematic improvement and subjective participation of citizens, which the political system of Russia is still not characterized by. The most useful research methods that author used in writing this article were the case study, the decision-making and systemic methods.